Fabrication and Electrochemical Characterization of Molecularly Alternating Self-Assembled Films and Capsules of Titania Nanosheets and Gold Nanoparticles - Zhou, Yong; Wang, Lian Z.; Ma, Ren Z.; Ebina, Yasuo; Takada, Kazunori; Sasaki, Takayoshi (Current Nanoscience, 2007)
A molecularly alternating self-assembled film and heterostructured capsule of titania nanosheets/gold nanoparticles has been successfully fabricated by layer-by-layer self-assembly of titania nanosheets and positively charged gold nanoparticles as electrostatic building blocks. The films were characterized with atomic force microscopy and UV-vis absorption spectroscopy. The nearly linear increase in both UV-vis absorbances as a function of the sequential assembly number demonstrates the regular growth of the composite film. The electrochemcial property of the fabricated (titania nanosheet/Au nanoparticle)n multilayer film was examined by measuring cyclic voltammograms. The heterostructured capsule from a UV-sensitive poly(methyl methacrylate) as a sacrificial template was characterized by field-emission scanning electron microscopy and transmission electron microscopy. The energy-dispersive X-ray spectrometer verifies the composition of Ti and Au elements of the heterostructured capsule.
Keywords: Capsules